Range extension of the endemic Sumatran admiral Vanessa samani (Hagen, 1895) (Lepidoptera: Nymphalidae) in Sumatra, Indonesia - Muhammad Iqbal; Pavel Kirillov; Pormansyah Pormansyah; Doni Setiawan; Guntur Pragustiandi; Arum Setiawan; Indra Yustian (Universitas Pakuan, 2022)
Sumatran Admiral Vanessa samani (Hagen, 1895) (Lepidoptera: Nymphalidae) is a butterfly endemic to Sumatra, and can only be found in the Karo Highlands (North Sumatra) and Kerinci Mountain (southwestern Sumatra). In this paper, we report two additional records of V. samani from the Aceh Province in northern Sumatra, and the Jambul Highlands of South Sumatra. These records significantly extend the range of distribution of this rare Sumatran highland species. We also report three plants presumed to be the host plants of V. samani in Sumatra: Boehmeria sp., Smilax sp. (Smilax leucophylla) and Anaphalis sp. (Anaphalis longifolia).